The False Promise of Adolescent Brain Science in Juvenile Justice - Maroney, Terry A. (2009)
Recent scientific findings about the developing teen brain have both captured public attention and begun to percolate through legal theory and practice. Indeed, many believe that developmental neuroscience contributed to the U.S. Supreme Court's elimination of the juvenile death penalty in Roper v. Simmons. Post-Roper, scholars assert that the developmentally normal attributes of the teen brain counsel differential treatment of young offenders, and advocates increasingly make such arguments before the courts. The success of any theory, though, depends in large part on implementation, and challenges that emerge through implementation illuminate problematic aspects of the theory. This Article tests the legal impact of developmental neuroscience by analyzing cases in which juvenile defendants have attempted to put it into practice. It reveals that most such efforts fail. Doctrinal factors hamstring most claims — for example, that persons with immature brains are incapable of forming the requisite mens rea for serious crimes. Limitations intrinsic to the science itself — for example, individual variation — also hinder its relevance and impact. These factors both explain why developmental neuroscience has had minimal effects on juvenile justice in the courts and illustrate why it generally should. Moreover, direct reliance on neuroscience as the metric for juvenile justice policy may jeopardize equality and autonomy interests, and brain-based arguments too frequently risk inaccuracy and overstatement. The cases also strongly suggest that neuroscience does not materially shape legal decision makers' beliefs and values about youthful offenders but instead will be read through the lens of those beliefs and values. Developmental neuroscience nonetheless can play a small role in juvenile justice going forward. Legislatures and courts may regard that science as one source among many upon which to draw when basing policy choices on assumptions about juveniles as a group. To go further is unwarranted and threatens to draw attention away from critical legal and environmental factors — good schools, strong families, economic opportunities, mental health care, humane sentencing regimes, and rehabilitative services — that are both more important and subject to greater direct control. Reprinted by permission of the publisher